ANALISIS MANAJEMEN IMPRESI PENGGEMAR K-POP DALAM MEMANIPULASI DIRI DI SOCIAL NETWORK SITE (SNS) - Lestari, Annisa Fitriana; Eriyanto, Eriyanto (Universitas Teuku Umar, 2020)
Various forms of internet products help people to have instant and easy activities, one of them is Social Network Site (SNS). Internet including SNS provides a place for users freedom of expression without having to be bound by rules like in the real world. Instagram as one kind of SNS, provides an opportunity for individuals to create more than one user account. This feature helps user to create an original account (rinsta) and fake account (finsta) that drives self-manipulation. Self-manipulation on real and fake Instagram accounts related to how individuals carry out impression management. Individuals set a good impression on the original account, while showing the true character on the fake account. Self-manipulation on the Internet more affects the psychological state of individuals to emerge different characters in offline, real and fake accounts. This character difference becomes a form of online disinhibition effect. K-Pop fans use variety of media to connect with their idols and fandoms, but they still have a concern of their self-image will be damaged in others people perspectives who are neutral or dislike K-Pop. The advantage of Instagram being able to have more than one account is a way out for K-Pop fans to manipulate themselves. This research was conducted using a qualitative approach with observations on real and fake K-Pop fan accounts, as well as interviews with users. The results of the study show that K-Pop fans use risnta as their front stage and finsta as their background to express their true self.